STRENGTHENING PANCASILA CHARACTER FOR MIGRANT CHILDREN AT THE SANGGAR BIMBINGAN AL AMIN MALAYSIA - Sri Kuswantono; Henny Herawaty BR Dalimunthe; Retno Dwi Lestari; Nurul Azima; Akmaludin (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract Children born to families of illegal Indonesian migrant workers (TKI) do not have access to education in Malaysia. Their limited bargaining power due to the absence of administrative documents results in these children being unable to receive proper education. The Sanggar Bimbingan (Guidance Studio) has become a non-formal education unit that provides basic life skills for these children. However, the implementation of Sanggar Bimbingan faces many challenges, such as the limited number of professional teachers, non-conducive learning environments, and scarce learning materials. Another issue is the limited knowledge about Indonesia as their homeland, posing a risk of eroding their Indonesian identity, particularly the values of Pancasila. This community service initiative aims to strengthen Pancasila Character through a project-based approach rich in cultural values. The activities were carried out at Sanggar Bimbingan Al Amin, Malaysia. The results show that the Pancasila Student Profile Project with the global diversity dimension was successfully achieved. This achievement is demonstrated by the learners' ability to name various traditional Indonesian clothing (C1-Remembering), group traditional clothing based on similarities in attire and ornaments used (C2-Understanding), identify characteristics of one of the chosen traditional outfits (C3-Applying), and explain to their peers about the selected traditional clothing (C4-Analyzing).   Abstrak Anak-anak yang lahir dari keluarga tenaga kerja Indonesia (TKI) ilegal tidak memiliki akses pendidikan di Malaysia. Rendahnya daya tawar karena ketiadaan dokumen administratif, mengakibatkan anak-anak ini tidak dapat menerima pendidikan yang layak. Sanggar Bimbingan telah menjadi unit pendidikan nonformal yang menyelenggarakan keterampilan dasar hidup bagi anak-anak ini. Namun, penyelenggaraan Sanggar Bimbingan menghadapi banyak tantangan, seperti terbatasnya jumlah guru profesional, lingkungan belajar yang tidak kondusif, dan terbatasnya bahan belajar. Permasalahan lain yang muncul ada terbatasanya pengetahuan mengenai Indonesia sebagai tanah air mereka. Hal ini menghadirkan risiko terkikisnya karakter Indonesia, terutama nilai-nilai Pancasila. Inisiatif pengabdian masyarakat ini bertujuan untuk memperkuat Karakter Pancasila melalui pendekatan berbasis projek yang kaya akan nilai budaya. Kegiatan ini dilaksanakan di Sanggar Bimbingan Al Amin, Malaysia. Hasil menunjukkan bahwa kegiatan Projek Profil Pelajar Pancasila dengan dimensi kebhinekaan global berhasil dicapai. Ketercapaian ini ditunjukkan dengan kemampuan peserta didik dalam menyebutkan ragam Pakaian Adat Indonesia (C1-Mengingat),  mengelompokkan pakaian adat berdasarkan kemiripan busana dan perhisasan yang digunakan (C2-Memahami),  mengidentifikasi ciri-ciri dari salah satu pakaian adat yang dipilih (C3-Menerapkan), dan  menjelaskan kepada teman mengenai pakaian adat yang dipilih. (C4-menganalisis).